(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The origin of human nature, the foundation for religious freedom. James Henry Rushbrooke and the struggle for religious freedom of Romanian Baptists. In this paper, „The Origin of Human Nature, Foundation for Religious Freedom. James Henry Rushbrooke and the Struggle for Religious Freedom of Romanian Baptists,” the author brings forth the personality and endeavors of the British Baptist minister James Henry Rushbrooke, who, from his leadership roles in the Baptist World Alliance during the interwar period, became the most loyal and fervent advocate for the Romanian Baptist in their struggles to obtain religious freedom. The foundation for Rushbrooke’s tireless work rests on the principle of freedom of conscience, which is capital for Baptist believers, who are convinced that the origin of human nature is the basis for human rights and implicitly for the freedom of conscience of each and every individual.